1985
DOI: 10.1080/07391102.1985.10508425
|View full text |Cite
|
Sign up to set email alerts
|

Temperature Jump Relaxation Studies on the Interactions Between Transfer RNAs with Complementary Anticodons. The Effect of Modified Bases Adjacent to the Anticodon Triplet

Abstract: We have used the temperature-jump relaxation technique to determine the kinetic and thermodynamic parameters for the association between the following tRNAs pairs having complementary anticodons: tRNA(Ser) with tRNA(Gly), tRNA(Cys) with tRNA(Ala) and tRNA(Trp) with tRNA(Pro). The anticodon sequence of E. coli tRNA(Ser), GGA, is complementary to the U*CC anticodon of E. coli tRNA(Gly(2] (where U* is a still unknown modified uridine base) and A37 is not modified in none of these two tRNAs. E. coli tRNA(Ala) has … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
19
0

Year Published

1993
1993
2022
2022

Publication Types

Select...
7
1
1

Relationship

0
9

Authors

Journals

citations
Cited by 39 publications
(19 citation statements)
references
References 46 publications
0
19
0
Order By: Relevance
“…A37 stabilises the intrinsically weak interaction of the A36-U base-pair (Jukes, 1973;Nishimura, 1972). Indeed, the presence of the ms 2 i 6 A37 modi®cation stabilises tRNA-tRNA dimers with complementary anticodons mainly due to an improved stacking of the hypermodi®ed nucleoside (Houssier & Grosjean, 1985;Vacher et al, 1984). Thus, the results from such model experiments suggest that the modi®cation of A37 to ms 2 io 6 A37 stabilises the 3 H stacking features of the anticodon and thereby improves its interaction with the codon.…”
Section: Effects Of the M 1 G37 Modificationmentioning
confidence: 78%
“…A37 stabilises the intrinsically weak interaction of the A36-U base-pair (Jukes, 1973;Nishimura, 1972). Indeed, the presence of the ms 2 i 6 A37 modi®cation stabilises tRNA-tRNA dimers with complementary anticodons mainly due to an improved stacking of the hypermodi®ed nucleoside (Houssier & Grosjean, 1985;Vacher et al, 1984). Thus, the results from such model experiments suggest that the modi®cation of A37 to ms 2 io 6 A37 stabilises the 3 H stacking features of the anticodon and thereby improves its interaction with the codon.…”
Section: Effects Of the M 1 G37 Modificationmentioning
confidence: 78%
“…In model experiments in which dissociation of tRNA dimers with complementary anticodons was monitored, it was shown that this modification stabilizes anticodon-anticodon interaction by increased stacking (63). Such experiments have also shown that the ms 2 group is the major stabilizing factor (39). Thus, the effects observed in the aforementioned in vivo and in vitro experiments with tRNA from a miaA mutant were expected to be primarily due to lack of the ms 2 group.…”
Section: A37 Instead Of Msmentioning
confidence: 89%
“…Interactions between E. coli tRNA Gly (with anticodon U*CC, where U* is modified) and tRNA Ser (with an unmodified GGA anticodon) were found to be highly stable [73]; the sole anticodon loop modification in this interaction is that of U34 in the first (wobble) position of the tRNA Gly anticodon, as indicated. Importantly, neither tRNA has a modified purine at position 37, leading the authors to state that, "the presence of three consecutive purines in the [tRNA Ser ] anticodon triplet together with the two purines on its 3' side may yield sufficient stability..." [74]. The interaction between wheat tRNA Gly and E. coli tRNA Ala (with unmodified GCC and GGC anticodons respectively) is also highly stable [75].…”
Section: Discussionmentioning
confidence: 99%